Physically based Impedance Modelling of Lithium-Ion Cells - Illig, Jörg (Schriften des Instituts für Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Werkstoffe der Elektrotechnik, 2014)
In this book, a new procedure to analyze lithium-ion cells is introduced. The cells are disassembled to analyze their components in experimental cell housings. Then, Electrochemical Impedance Spectroscopy, time domain measurements and the Distribution function of Relaxation Times are applied to obtain a deep understanding of the relevant loss processes. This procedure yields a notable surplus of information about the electrode contributions to the overall internal resistance of the cell.